Penerapan media pembelajaran magic box untuk meningkatkan hasil belajar siswa sekolah dasar - septiani, erlyna; Desty Dwi Rochmania; Hawwin Fitra Raharja (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The aim of this research is to determine how effective the Magic Box media is using the contextual learning model for science and science learning outcomes in class IV elementary school. Quantitative research is the type of research used. By using a pre-experimental design, one group pretest and post-test. From the results of the t test calculation with dk = 18, sig level 5%, the ttable value = 1,734 is obtained, from the t test results the tcount = 16,950 is obtained. The tcount>ttable value is 16,950 > 1,734, so it can be interpreted that HO is rejected and Ha is accepted. The results obtained from the completeness test average pretest 56.0 and posttest 90.5. It can be concluded that the Magic Box media with a contextual learning model approach is effective on science and science learning outcomes regarding body parts of plants in class IV elementary school. Therefore, fourth grade elementary school students can use Magic Box media to improve their high-level thinking abilities. Keywords: Implementation, Effectiveness, Magic Box, Learning Results.